DIRECT AND INDIRECT SATIRE AS IDEOLOGICAL CRITIQUE IN TAIKA WAITITI’S JOJO RABBIT: A PRAGMATIC ANALYSIS - Cindy Miwi Lestari; Abd. Halim (Faculty of Languages and Literature, Universitas Negeri Makassar, 2026)
This study examines the construction and pragmatic functions of satire in Taika Waititi’s film Jojo Rabbit (2019). It addresses two questions: (1) what forms of satire are represented in selected scenes, and (2) what pragmatic functions do these satirical representations perform in criticizing Nazi ideology and wartime indoctrination? The study employed a descriptive qualitative design. The data consisted of eight purposively selected scenes containing verbal irony, incongruity, exaggeration, parody, understatement, or contrasts between literal expression and contextual meaning. Data were collected through repeated viewing, transcription, timestamping, and contextual note-taking. The analysis combined Abrams and Harpham’s distinction between direct and indirect satire with a pragmatic interpretation of utterances, co-text, speaker relationships, narrative situations, and socio-historical context. The findings show that direct satire exposes prejudice through explicit reversal and confrontational responses, whereas indirect satire operates through incongruous characterization, naïve dialogue, parody, understatement, and visual contrast. Across both forms, satire performs four interconnected functions: exposing dehumanizing propaganda, reducing ideological authority to absurdity, destabilizing indoctrinated beliefs, and restoring empathy through the recognition of shared humanity. The study argues that the film’s satire constructs ideological criticism not by trivializing history, but by using the interaction between humor and context to represent extremist reasoning as contradictory and morally indefensible. These findings contribute to pragmatic studies of cinematic discourse by demonstrating that satirical meaning emerges from the relationship among utterances, narrative situations, character knowledge, and historical ideology.